ANALISIS PENGARUH BRAND AWARENESS, BRAND IMAGE, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SAMASE DI JAKARTA - Rifqi Febriansyah (2022)
The demand for Muslim clothing is increasing. This is because the number of Muslim population also increases every year so fashion companies must be able to meet consumer needs. Samase is a fashion company that is involved in fulfilling consumer rights, trying to meet the demands of Muslim consumers. This is evidenced by the many agents/distributors spread especially in the DKI Jakarta area. This research uses quantitative methods that aim to find out, prove and analyze the influence of brand awareness, brand image and price on purchasing decisions for samase products in Jakarta. By using the purposive sampling method, the number of samples in this study was 100 respondents. To process and analyze the data that has been collected, namely by using descriptive analysis techniques and inferential analysis, namely by using the SmartPLS application (V.3.29). The results in this study reveal that: (1) Brand awareness has a positive and significant influence on purchase decisions with a path coefficient of 0.515. (2) Brand image has a positive and significant impact on purchase decisions with a path coefficient of 0.286. (3) Price has a positive and significant influence on purchase decisions with a path coefficient of 0.141. Meanwhile, brand awareness, brand image and price together contributed 0.733 (73.3%) to the decision, while the remaining 0.267 (26.7%) was influenced by other factors outside this research model.